Programmable 3D optical fields for trapping and nonlinear multiphoton processes - Bautista, Godofredo S. Jr. (Quezon City National Institute of Physics, College of Science, University of the Philippines Diliman, 2009)
The advent of ultrafast technology or femtosecond lasers has extended the applications of near-infrared (NIR) lasers from optical manipulation to nonlinear processes particularly in microsurgery and microfabrication. In this dissertation, I propose the use of 3D optical fields that employ programmable optical devices for optical trapping, microsurgery and two-photon photopolymerization.
Thesis (Ph.D. Physics)-- University of the Philippines Diliman
Keywords: Femtosecond lasers; Molecular imaging; Near infrared optical imaging